Influence of gas flow inside circular tube using computational fluid dynamics for graphene synthesis via chemical vapour deposition - Muhammad Naqib Osman (Kulliyah of Engineering,International Islamic University Malaysia, 2021)
Since its discovery in 2004, graphene has been tipped as the material that can boost various applications' development. Among the methods developed to produce graphene in large-scale is chemical vapour deposition (CVD). CVD is viewed as the most cost-efficient method besides having the potential to synthesize high-quality graphene. Despite this potential, it requires excellent control in various aspects, including fluid dynamics inside the CVD tube. Further studies need to be done especially near the substrate to understand further the effect of fluid dynamics on the graphene synthesis process via CVD. One of the subsidiaries of fluid dynamics near the substrate was the boundary layer thickness. This is the first layer where carbon needs to pass through to be at the substrate's surface. Changing the tilting angle is one of the ways to change the boundary layer thickness. In this study, the simulation was done for horizontal CVD with different tilting angle, and then graphene was synthesized in the lab based on the simulation results. This is to understand the effect of substrate tilting to the fluid behaviour inside the CVD tube and the graphene produce. The simulation was done using ANSYS® FLUENT where a 1m tube was divided into three sections which are the calm, heating and outlet section. A constant temperature of 1273K was supplied at the heating section wall, and the other two sections were exposed to room temperature. A substrate was placed in the heating section with a tilting angle of 8°,15°,30°,45°,60° and 75°. Based on the simulation at a 0° angle, the boundary layer thickness becomes thicker as the flow moves from the front to the rear of the substrate. For other tilting angles, the boundary layer thickness became thinner as the flow moved from the front to the end of the substrate. Higher tilting angle produced a thinner boundary layer, but the non-uniformity of the boundary layer thickness over the substrate surface also became more prominent. Tilted substrate also caused vortices at the side of the substrate where the larger the tilting angle, the larger vortices produced. Therefore, lower substrate angle was preferred for graphene synthesis as it has a more uniform boundary layer and smaller vortices. For the synthesis process, the 1cm x 1cm copper substrate was placed inside the CVD tube with a tilting angle of 8° and 15° with a flow rate of 100 sccm, 200sccm, and 300sccm for each synthesis process. A larger substrate angle was also chosen, which is 60° but only for 300 sccm of flow rate. Based on the Raman spectroscopy result, higher velocity will give thinner graphene for 8° and 15° substrate angle. For 8° substrate angle, the defect ratio increases as the flow rate increase while for 15°, it is vice versa. The graphene produce on top of the 8° and 15° substrate is constantly thin throughout the substrate, but for 60° substrate angle, the graphene becomes thinner from the front to the rear of the substrate. The defect on graphene produce on 60° substrate is also very high. This shows that the tilting angle plays a vital role in changing the graphene quality produced via CVD.